Residents’ Attitudes toward Tourism Development and Impacts in Koti-Kanasar, Indroli, Pattyur Tourism Circuit of Uttarakhand State, India - Bagri, S.C.; Kala, Devkant (PASOS Revista de Turismo y Patrimonio Cultural, 2015)
Indian Himalaya is characterized by tourism potential which provides good opportunity for economic development in long run. Considering vast potential for tourism development, Koti?Kanasar, Indroli, Pattyur circuit of Uttarakhand has been identified as an area for rural tourism promotion by Indian Ministry of Tourism. Since the circuit is in involvement stage of development, it is important to ensure sustainable development of tourism for which understanding of residents’ attitude is very essential. This study examined attitude of residents towards tourism impacts and influence of demographic attributes on their attitude. The study reveals that infrastructure facilities, design and package of rural tourism products, skill development programs for stakeholders and specific marketing campaigns are essential to tourism development. Findings indicate that residents understand the extent of tourism impacts in their mountainous region with respect to economic, social and environmental dimensions. Study also reveals that although locals want to increase tourism gains with corresponding effort to reduce consequences deprived, their perceived impacts of tourism vary across their demographic variables.